Multiple-cue illumination estimation in textured scenes - Li, Yuanzhen; Lin, Steve; Lu, Hanqing; Shum, Harry (International Conference on Computer Vision (ICCV), 2003)
In this paper, we present a method that integrates cues from shading, shadow and specular reflections for estimating directional illumination in a textured scene. Texture poses a problem for lighting estimation, since texture edges can be mistaken for changes in illumination condition, and unknown variations in albedo make reflectance model fitting impractical. Unlike previous works which all assume known or uniform reflectance, our method can deal with the effects of textures by capitalizing on physical consistencies that exist among the lighting cues. Since scene textures do not exhibit such coherence, we use this property to minimize the influence of texture on illumination direction estimation. For the recovered light source directions, a technique for estimating their intensities in the presence of texture is also proposed.